2016
DOI: 10.2105/ajph.2016.303472
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Association of Human Papillomavirus Vaccination with Cervical Dysplasia Prevalence in the United States, 2007–2014

Abstract: Decreases in high-grade lesions reflected their greater association with human papillomavirus types 16 and 18, compared with low-grade lesions, providing ecological evidence of population effectiveness of human papillomavirus vaccination among young, privately insured women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 39 publications
1
33
0
1
Order By: Relevance
“…In our analysis, reductions in 4vHPV-type prevalence remained significant after multivariable adjustment for both demographics and sexual behaviors. Our findings of declining prevalence of 4vHPV types among females aged 14–19 years and 20–24 years are consistent with ecologic studies that have documented declines in genital warts and precancer lesions among women in their early 20s; however, these prior studies did not adjust for possible changes in sexual behavior [26, 27]. The specificity of declines to 4vHPV types in our adjusted analyses further supports the conclusion that the vaccination program is primarily responsible for the observed declines in HPV prevalence.…”
Section: Discussionsupporting
confidence: 87%
“…In our analysis, reductions in 4vHPV-type prevalence remained significant after multivariable adjustment for both demographics and sexual behaviors. Our findings of declining prevalence of 4vHPV types among females aged 14–19 years and 20–24 years are consistent with ecologic studies that have documented declines in genital warts and precancer lesions among women in their early 20s; however, these prior studies did not adjust for possible changes in sexual behavior [26, 27]. The specificity of declines to 4vHPV types in our adjusted analyses further supports the conclusion that the vaccination program is primarily responsible for the observed declines in HPV prevalence.…”
Section: Discussionsupporting
confidence: 87%
“…No declines were observed in the oldest age group who were not age-eligible to receive the HPV vaccine during the surveillance period in this analysis. In prior studies of CIN2þ incidence, vaccine impact has not yet been observed among women over the age of 24 years, and rates of CIN2þ calculated among screened women in age groups 25 and older have actually increased (9,10,17). By histologic grade, declining trends were observed in CIN2 and CIN2/3 only.…”
Section: Discussionmentioning
confidence: 93%
“…Previously, vaccine impact on CIN2þ has been observed through a declining incidence among screened young women. Within eight years of vaccine introduction, significant declines in the rate of CIN2þ were observed in a statewide registry among screened [15][16][17][18][19] year olds and 20-24 year olds, (9) and in [15][16][17][18][19] year olds in a large claims database for the privately insured (17). HPV-IMPACT has also observed a decline in rates of CIN2þ among young women (8,10,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rate ratio (age-adjusted) dropped significantly from 0.91 to 0.36 in women aged 15–17 years old. Subsequent studies have achieved similar results [56, 57]. More recently, a systematic review confirmed the positive effect of the HPV vaccines against CIN, showing the efficacy of 95% (CIN1+), 97% (CIN2+), and 95% (CIN3+) [58].…”
Section: Data From Real Worldmentioning
confidence: 75%